Space configurations for empowering university-community interactions - Dorland, Jens; Clausen, Christian; Jørgensen, Michael Søgaard (Science and Public Policy, 2019)
Some see universities as a possible source of solutions to enable a sustainable transition and overcome societal challenges. Findings from three multisite case studies of Desis Labs, FabLabs, and Science Shops shed light on how universities can help empower communities and solve societal challenges locally. Adopting a sociotechnical and flat relational perspective inspired by science and technology studies (STS), we focus on the material and spatial aspects of how these spaces are configured, thereby ensuring practical relevance for policy makers and practitioners. Applying an analytical generalization methodology, we condense the qualitative data into a typology of three ideal space-types (i.e. affording, mediating, and impact-oriented) that represent specific configurations of actors, researchers, students, communities, spaces, infrastructure, equipment, facilitators, etc. The ideal space-types empower communities in different ways, require different resources to create and operate, and translate differently into specific local contexts.
Number: 5
Keywords: Communauté d'innovation; Laboratoire vivant; Méthodes; Réservé UdeM; Rôle des universités; Université

À quoi sert l'innovation sociale - Maison de l'innovation sociale (2021)
L’histoire a vu son lot d’innovations technologiques et scientifiques dans toutes les époques et sphères de la société : dans les sciences, le transport, les infrastructures, la technologie, les communications et d’autres encore.
Keywords: Communauté d'innovation; Histoire; Innovation sociale; Invention; Libre accès; Montréal; Québec

Shaping social innovation in local communities: The contribution of intermediaries - Cibin, Roberto; Robinson, Sarah; Teli, Maurizio; Linehan, Conor; Maye, Laura; Csíkszentmihályi, Christopher (Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society, 2020)
Participatory social innovation projects often involve the coming together of design researchers, community development groups, and community members to develop (often technological) solutions to social problems or challenges. “Intermediaries” are specific individuals and organisations who contribute to these projects by translating intentions, values and experiences between design researchers and communities. Previous research has not yet critically examined the role of intermediaries in such projects. This paper does so in a project carried out in rural areas of Europe, which sought to test and develop a technology to support the creation of FM community radio stations in isolated areas. We present the project as a biography of infrastructures to provide an account of intermediaries’ interactions during the project's unfolding. We find that how intermediaries shape the social base and ends of the project, and the interpretation of the technology involved, is influenced by their position, goals, and relationships in the process.
Keywords: Communauté d'innovation; Europe; Libre accès

À quoi sert l'innovation sociale - Maison de l'innovation sociale
L’histoire a vu son lot d’innovations technologiques et scientifiques dans toutes les époques et sphères de la société : dans les sciences, le transport, les infrastructures, la technologie, les communications et d’autres encore.
Keywords: Communauté d'innovation; Histoire; Innovation sociale; Invention; Libre accès; Montréal; Québec

Les communautés d’innovation : de la liberté créatrice à l’innovation organisée - Parmentier, Guy (Management international / International Management / Gestiòn Internacional, 2017)
Un article de la revue Management international / International Management / Gestiòn Internacional, diffusée par la plateforme Érudit.
Publisher: HEC Montréal
Keywords: Co-création; Communauté d'innovation; Innovation; Libre accès; Méthodes

Academic Entrepreneurship and Community Engagement: Scholarship in Action and the Syracuse Miracle - Kingma, Bruce (Cheltenham, U.K. and Northampton, Mass.: Elgar, 2011)
Eleven papers explore research in entrepreneurship and community engagement in the context of Syracuse University's Scholarship in Action Model, which emphasizes sustainable campus-community entrepreneurial partnerships and applied research on the outcomes of these. Papers discuss the five keys to success in academic entrepreneurship; transforming a professional curriculum through engagement with practice–the Global Enterprise Technology Program at Syracuse University; tapping our fountain of youth–the guiding philosophy and first report on the Syracuse Student Startup Accelerator; Syracuse University Technology Commercialization Clinics; community development law and legal education; the Syracuse Miracle–inspiring entrepreneurs through conversations; the South Side Newspaper Project; bridging a traumatic past to an envisioned future–a case study of social entrepreneurship; inclusive entrepreneurship; the role of information and motivation in the process of innovation; and students serving as catalysts within a teacher education innovation.
Accès 1 usager à la fois sur ebook Central
Keywords: Communauté d'innovation; Engagement communautaire; Entrepreneuriat; Idéation; dialogue et maillage; Partenariat; Réservé UdeM; Rôle des universités; Transfert; Université; États-Unis

Space configurations for empowering university-community interactions - Dorland, Jens; Clausen, Christian; Jørgensen, Michael Søgaard (Science and Public Policy, 2019)
Some see universities as a possible source of solutions to enable a sustainable transition and overcome societal challenges. Findings from three multisite case studies of Desis Labs, FabLabs, and Science Shops shed light on how universities can help empower communities and solve societal challenges locally. Adopting a sociotechnical and flat relational perspective inspired by science and technology studies (STS), we focus on the material and spatial aspects of how these spaces are configured, thereby ensuring practical relevance for policy makers and practitioners. Applying an analytical generalization methodology, we condense the qualitative data into a typology of three ideal space-types (i.e. affording, mediating, and impact-oriented) that represent specific configurations of actors, researchers, students, communities, spaces, infrastructure, equipment, facilitators, etc. The ideal space-types empower communities in different ways, require different resources to create and operate, and translate differently into specific local contexts.
Analyse centrée sur trois types d’approches collaboratives et issues des résultats et constats du projet TRANSIT (terminé en 2017) : 1. Science Shops, 2. FabLabs, Desis Labs
Keywords: Communauté d'innovation; Laboratoire vivant; Méthodes; Réservé UdeM; Rôle des universités; Université

Shaping social innovation in local communities: The contribution of intermediaries - Cibin, Roberto; Robinson, Sarah; Teli, Maurizio; Linehan, Conor; Maye, Laura; Csíkszentmihályi, Christopher (Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society, 2020)
Participatory social innovation projects often involve the coming together of design researchers, community development groups, and community members to develop (often technological) solutions to social problems or challenges. “Intermediaries” are specific individuals and organisations who contribute to these projects by translating intentions, values and experiences between design researchers and communities. Previous research has not yet critically examined the role of intermediaries in such projects. This paper does so in a project carried out in rural areas of Europe, which sought to test and develop a technology to support the creation of FM community radio stations in isolated areas. We present the project as a biography of infrastructures to provide an account of intermediaries’ interactions during the project's unfolding. We find that how intermediaries shape the social base and ends of the project, and the interpretation of the technology involved, is influenced by their position, goals, and relationships in the process.
Keywords: Communauté d'innovation; Europe; Idéation; dialogue et maillage; Libre accès; Étude de cas